The Candymakers and the Great Chocolate Chase - Mass, Wendy, 1967- (Little, Brown and Company, 2016)
"It has been a few months since the nationwide New Candy Contest, and Logan, Miles, Philip, and Daisy have returned to their regular lives. But when the winning candy bar comes down the conveyor belt at the Life Is Sweet candy factory, Logan realizes something's very wrong. . . . When the Canymaker announces that they will be going on tour to introduce the new candy bar, the four friends see this as an opportunity to make things right. But with a fifty-year-old secret revealed and stakes higher for each of them than they ever imagined, they will have to trust one another--and themselves--in order to face what lies ahead."--Book jacket flap.